2020
DOI: 10.1021/acs.iecr.9b07110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Diffusion of Disperse Dye in a Polyethylene Terephthalate Film from an Infrared Spectroscopic Perspective

Abstract: The diffusion behavior of a typical disperse dye, disperse red 9 (DR 9), in the polyethylene terephthalate (PET) film at different temperatures was investigated by attenuated total reflection–Fourier transform infrared spectroscopy and 2D correlation spectroscopy (2Dcos) analyses. According to the Fickian diffusion model, the calculated diffusion coefficients of DR 9 in the PET film at different temperatures were observed to increase with temperature, which might be attributed to the increased free volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In this context, it is widely held that elevated dyeing temperatures must be employed in HT dyeing processes because of the very low diffusional behaviour of the dyes within the structurally recalcitrant PET polymer. Evidence to support this generally held view is provided by the findings 4‐10 that the increase in disperse dye diffusion within PET substrates, as expressed in terms of the diffusivity of the dye molecules, that accompanies an increase in dyeing temperature, is related to the temperature‐dependent relaxation processes that occur within the substrate, as expressed in terms of polymer chain segmental mobility and available free volume, in which fibre glass transition assumes a pivotal role.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, it is widely held that elevated dyeing temperatures must be employed in HT dyeing processes because of the very low diffusional behaviour of the dyes within the structurally recalcitrant PET polymer. Evidence to support this generally held view is provided by the findings 4‐10 that the increase in disperse dye diffusion within PET substrates, as expressed in terms of the diffusivity of the dye molecules, that accompanies an increase in dyeing temperature, is related to the temperature‐dependent relaxation processes that occur within the substrate, as expressed in terms of polymer chain segmental mobility and available free volume, in which fibre glass transition assumes a pivotal role.…”
Section: Introductionmentioning
confidence: 95%
“…To further study the crucial role of Lewis acidbase pairs in the ring-opening of PO and the CO 2 cycloaddition reaction, in-situ diffuse reflectance infrared Fouriertransform spectroscopy (DRIFT) was performed to study the reaction intermediates by observing bonding alterations in the catalytic reaction. As shown in Figure 4(a), after 30 min treatment with PO under a carbon dioxide atmosphere at 423 K, five new peaks at 670, 1090, 1255, 1410, 1510, and 1680 cm -1 appeared, corresponding to the vibration of C-Br, C-O, C-O-C, carbonate, and C = O, respectively [30][31][32][33][34]. Of note, the formation of C-Br demonstrated that Br atoms acted as a Lewis base sites to attack the carbon atoms in the epoxide, which played a key role in the ring-opening of the epoxide.…”
Section: Resultsmentioning
confidence: 99%
“…47 The pronounced temperature dependency of disperse dye diffusivity (Table 5), which is generally observed for all dye/fibre systems 5 can be attributed to both the greater kinetic energy of the dye molecules and their enhanced aqueous solubility, as well as enthalpically favoured disperse dye disaggregation and increased levels of both water-induced PET fibre swelling and fibre plasticisation. However, it is also widely accepted that disperse dye diffusivity within polyester materials is primarily governed by the relaxation times of the structural relaxations taking place within the PET polymer (e.g., 140,142,143,[152][153][154][155][156][157][158][159][160][161][162][163] ); this important facet of the disperse dye/PET fibre system is discussed in Section 4.3.…”
Section: Effect Of Temperaturementioning
confidence: 99%